2013
DOI: 10.1177/1753193413501588
|View full text |Cite
|
Sign up to set email alerts
|

Intercostal and pectoral nerve transfers to re-innervate the biceps muscle in obstetric brachial plexus lesions

Abstract: In obstetric brachial plexus lesions with avulsion injury, nerve grafting for biceps muscle re-innervation may not be possible owing to the unavailability of a proximal stump. In such cases, the intercostal nerves or medial pectoral nerve can serve as donor nerves in an end-to-end transfer to the musculocutaneous nerve. The present study reports the results of both techniques from a single institution in a consecutive series of 42 patients between 1995 and 2008. From 1995 to 2000 we always used the intercostal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 34 publications
1
27
1
2
Order By: Relevance
“…In the reconstruction of elbow flexion in OBPP patients, transfer of either the MPN or the ICN to the MCN resulted in satisfactory function. 12 In adults, MPN-MCN transfer has yielded either equivocal or better results (92% satisfactory) when compared with ICN-MCN transfer (82% satisfactory) and has become the preferred method for either C5 to C6 or C5 to C7 injuries by some physicians. 12 This observation is likely due to the greater number of motor axons in the MCN when compared with the ICN.…”
Section: Elbow Flexionmentioning
confidence: 98%
See 3 more Smart Citations
“…In the reconstruction of elbow flexion in OBPP patients, transfer of either the MPN or the ICN to the MCN resulted in satisfactory function. 12 In adults, MPN-MCN transfer has yielded either equivocal or better results (92% satisfactory) when compared with ICN-MCN transfer (82% satisfactory) and has become the preferred method for either C5 to C6 or C5 to C7 injuries by some physicians. 12 This observation is likely due to the greater number of motor axons in the MCN when compared with the ICN.…”
Section: Elbow Flexionmentioning
confidence: 98%
“…12 In adults, MPN-MCN transfer has yielded either equivocal or better results (92% satisfactory) when compared with ICN-MCN transfer (82% satisfactory) and has become the preferred method for either C5 to C6 or C5 to C7 injuries by some physicians. 12 This observation is likely due to the greater number of motor axons in the MCN when compared with the ICN. In addition, it has been shown that the use of 3 ICNs produces better results than the use of only 2 nerves.…”
Section: Elbow Flexionmentioning
confidence: 98%
See 2 more Smart Citations
“…At least two of them per recipient nerve are needed [24,124]. They have been used to re-innervate many nerves, like the AXN [89,92], MCN [24,105,106,[124][125][126], TLH [92,118,119], TDN [89,127] and SSN [90,91]. Their sensory branches can be used to recover some limb sensation, ameliorating the neuropathic pain.…”
Section: Intercostal Nerve Transfersmentioning
confidence: 99%